Analysis of leading sector of Jambi City - Hardiani Hardiani; Tona Aurora Lubis (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2017)
This study aims to analyze the leading sectors in the city of Jambi. The main data used is GDP data of Jambi City series 2010 for the period of 2012-2014. Analysis tool that is used are Location Quotient, Shift Share, Klassen Typology and Overlay Analysis. The results of the analysis found that of the 14 basic sectors in Jambi City (based on LQ analysis), there are four priority sectors namely electricity and gas procurement, building, large and retail trade, car and motorcycle repairs, health service, and social activities. Keywords: Location Quotient, Shift Share, Klassen Tipology, Overlay Analysis